Virtual Processes in Aesthetics (2021)
The following article draws on the theoretical framework developed within the research project on Digital Aesthetics, put in place by the Research Group "Communication Culture and Aesthetics" of the Social Communication-Journalism Program of the UCPR and of the Master's Program in Multimedia Education at the University of Caldas. This theoretical proposal looks at the concepts that founded the aesthetics of digital media and discusses the phenomena that shape the new forms of symbolic representation and production of meaning, leading to the current aesthetic called Media Art. The article shows how this new aesthetic form is based on concepts such as virtualization processes, interactivity, participation, structure and feedback information between producers and audiences.